Pelatihan Peningkatan Kemampuan Pengelolaan Keuangan & Perencanaan Usaha pada KPM PKH: Financial Management, Business Planning,Family Hope Program (PKH), Financial Literacy, Budgeting, Debt Management, Training Program, Low-Income Families - Vina Andita; Endah Budiastuti (PT. Berkah Digital Teknologi, 2023)
This journal article presents the results of a training program aimed at enhancing the financial management and business planning skills of households receiving the Family Hope Program (PKH) in Sarajaya Village, LemahAbang Sub-district, Cirebon Regency. The training addressed the challenges faced by low-income families in managing their finances effectively and provided them with the knowledge and skills needed for better financial planning and management. The program targeted PKH recipient mothers and aimed to improve their financial literacy, budgeting, debt management, and business planning capabilities. The training utilized various methods including lectures, group discussions, simulations, and practical exercises. The outcomes indicated significant improvements in participants' financial understanding, budgeting skills, and economic well-being. The article concludes by suggesting continuous and expanded training, practical integration, regular discussions, local financial institution partnerships, and ongoing evaluation for sustained positive impacts on the financial well-being of PKH recipient households.